2019
DOI: 10.1016/j.rmed.2019.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Association between vitamin D status and asthma control: A meta-analysis of randomized trials

Abstract: Background: There is a controversy in terms of the efficacy of vitamin D supplementation in improving asthma symptom control. Moreover, whether there is a difference in the treatment effect with respect to baseline vitamin D status remains unknown. This meta-analysis was to assess the correlations of vitamin D status with asthmarelated respiratory outcomes. Methods: PubMed, EMBASE, and Cochrane Library were searched for randomized controlled trials of vitamin D supplementation in patients with asthma. Primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 43 publications
1
45
3
3
Order By: Relevance
“…Indeed, many RCTs of vitamin D supplementation to improve asthma control and exacerbations have been completed and these studies have reported a mixture of positive and negative results. However, several meta-analyses show that vitamin D supplementation significantly reduced the rate of severe exacerbations in patients with asthma [109][110][111][112][113]. Whether these effects are only observed in patients with vitamin D deficiency, as was shown in COPD, is less clear since only two studies performed subgroups analysis, showing conflicting results [112,113].…”
Section: Vitamin D In Asthma Exacerbationmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, many RCTs of vitamin D supplementation to improve asthma control and exacerbations have been completed and these studies have reported a mixture of positive and negative results. However, several meta-analyses show that vitamin D supplementation significantly reduced the rate of severe exacerbations in patients with asthma [109][110][111][112][113]. Whether these effects are only observed in patients with vitamin D deficiency, as was shown in COPD, is less clear since only two studies performed subgroups analysis, showing conflicting results [112,113].…”
Section: Vitamin D In Asthma Exacerbationmentioning
confidence: 99%
“…However, several meta-analyses show that vitamin D supplementation significantly reduced the rate of severe exacerbations in patients with asthma [109][110][111][112][113]. Whether these effects are only observed in patients with vitamin D deficiency, as was shown in COPD, is less clear since only two studies performed subgroups analysis, showing conflicting results [112,113]. While the most recent meta-analysis clearly concluded that vitamin D supplementation played a role in reducing the rate of exacerbations particularly in patients with vitamin D insufficiency [113], subgroup analysis using individual patient data did not result in such a firm conclusion [112].…”
Section: Vitamin D In Asthma Exacerbationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed that children who have taken supplementary vitamin D during the first year of life have a lower risk of asthma at 31 years of age, but there was no report of vitamin D levels during this period [29]. A meta-analysis of randomized trials show the rate of asthma exacerbation can reduce by vitamin D supplementation especially in patients with vitamin D insufficiency [30]. Litonjua (2019) suggested vitamin D supplementation can prevent asthma and wheeze in early life, and may help in treatment of asthma [31].…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analyses show that vitamin D deficiency is associated with a higher risk of sleep disorders [2] and may be related to autoimmune thyroid disease [3], whereas high vitamin D serum levels have a protective effect on breast cancer in premenopausal women [4]. They also indicate that vitamin D supplementation significantly reduces cancer mortality [5], as well as the rate of asthma exacerbations [6]. Taking it into account, scientists agree that vitamin D goes beyond influencing bone health only [7,8].…”
Section: Introductionmentioning
confidence: 99%